PENGARUH SUPERVISI AKADEMIK, KOMPETENSI GURU DAN KEDISIPLINAN TERHADAP KINERJA GURU SMA NEGERI 3 SLAWI KABUPATEN TEGAL - Sussono Hadi; Tukiran Tukiran; Budi Yuwono (Khazanah Pendidikan, 2009)
This research is aimed at finding out the impact of academic supervision, teacher’s competence, and discipline towards the performance of teachers of SMA Negeri 3 Slawi, Tegal. This research used survey method. The data was collected using questionnaire and observation. There were 52 teachers as respondents. The data analysis used was percentage, multiple linear regression, F test and t test. The finding was : 1) academic supervision, teacher’s competence and discipline of SMA 3 Slawi teachers were very good, 2) academic supervision, teacher’s competence, and discipline together had impact towards teachers’ performance, 3) academic supervision, teacher’s competence, and discipline separately had impact on teachers’ performance, and 4) discipline had the strongest impact towards teachers’ performance. With this result it is suggested that the Diknas (the regential ministry of education) intensify the academic supervision, continually developing teacher’s competence, and enforcing discipline on teachers and schools. Key words: academic supervision, competence, discipline, teacher’s performance